Simulation and Analysis of Water Consumption for Rice Production in Downstream Lancanng-Mekong River Basin under the Influence of Climate Change - XIE Shimeng; LIU Dengfeng; LIU Hui; HU Hongchang; DONG Zhiqiang; WANG Tianci; MING Guanghui (Renmin Zhujiang)
Agriculture water consumption is the main sector of socio-economic water consumption.The impact of climate change on agriculture water consumption may change the situation of water supply and demand in a region.The downstream Lancang-Mekong River Basin is selected as the study area.Based on the ERA5-Land dataset and the latest CMIP6 climate projection data,three emission scenarios (SSP1-2.6,SSP2-4.5,and SSP5-8.5) are selected in this study,and the AquaCrop model is used to separate non-productive soil evaporation from productive crop transpiration.The total transpiration during the rice growth period is taken as water consumption for rice production,and the historical and subsequent water consumption for rice production in the downstream Lancang-Mekong River Basin is simulated.The changes in water consumption for rice production and its correlation with temperature,precipitation,and CO2 concentration are analyzed.The results show that the water consumption for rice production in the downstream Lancang-Mekong River Basin is manifested as more water consumption in the north and less water consumption in the south and has an overall decreasing trend annually.The trend is more obvious under the SSP5-8.5 scenario.In the SSP5-8.5 scenario,water consumption for rice production will reduce by 29.7% in the downstream Lancang-Mekong Basin in the far future.Compared with temperature and precipitation,the strongest correlation is found between water consumption for rice production and CO2 concentration.In the far future of the SSP5-8.5 scenario,the correlation coefficient is-0.875 in Thailand and less than-0.9 in other countries in all seasons.